(untitled) (Research, Society and Development, 2025)
Escherichia coli (E. coli) is a bacterium often found in the gastrointestinal tract of broilers. Although many strains are harmless, pathogenic strains can cause serious infections, the prevalence of which is influenced by external factors such as management, hydration, feeding and, crucially, disinfection of the environment. E. coli infections cause economic losses to poultry farming due to increased mortality and weight loss in surviving birds. The general objective of this work is to report a case of E. coli occurrence in broiler birds at Granja Cortez, located in the municipality of Pimenta Bueno-RO. The Methodology classifies the study as a case report, using a descriptive and retrospective approach. The clinical findings in the infected birds, such as swelling with accumulation of abdominal fluid, lethargy and respiratory distress, were consistent with the symptoms described in the literature. The diagnosis was established through necropsy in ten birds, which revealed opaque air sacs with yellow dots (Aerosacculitis) and inflammation in the respiratory system, which confirms the versatility of colibacillosis in causing systemic conditions. The treatment carried out with the infusion of antibiotics (amoxicillin and oxytetracycline) in drinking water for seven days resulted in the improvement of the birds and in the reduction of the mortality rate, confirming the effectiveness of the conduct. The outbreak emphasizes that, despite the high technology of the facilities, the success of production depends intrinsically on prophylaxis and strict sanitary management, such as impeccable biosecurity and guarantee of water quality and hygiene.